Conocimientos y actitudes en prevención sobre vih/sida en estudiantes de 19 a 24 años, de las facultades relacionadas y no relacionadas a las ciencias de la salud de la universidad nacional de Trujillo, 2007 - Rodríguez Bocanegra, Karin Giovana (2010)
In the following investigation of descriptive type, the population of study was constituted by students of The National University of Trujillo and there was carried out the selection of the sample, using random stratified sampling, which constituted 667 students from 19 to 24 years old of the related and not related Faculties to the Sciences of the Health; belonging 50.2 % to the feminine kind and 49.8 % to the masculine kind. The aim of the study was to establish the difference between the level of knowledge and attitudes in prevention on HIV / AIDS in the different faculties. The compilation of information was realized between April-July of 2007, applying an anonymous survey validated by the Test of Alpha Crombach. It was found as result that the students of the related faculties obtained in knowledge 14.20 points, whereas the students of the not related faculties 12.98. With regard to the attitude, the students of the related faculties obtained 0.67 points, whereas the students of the not related faculties 0.64. Also there was demonstrated that to major level of knowledge major level of attitude exists in prevention on HIV / AIDS, being in this way demonstrated the association of the variables in this study.